2012
DOI: 10.1007/s11356-011-0704-0
|View full text |Cite
|
Sign up to set email alerts
|

Study on the spectral and Cu (II) binding characteristics of DOM leached from soils and lake sediments in the Hetao region

Abstract: Two defined peaks, at wavelengths of 260∼300 nm (peak I) and 300∼350 nm (peak II), could be identified for soil DOM at a Δλ value of 30 nm. In sediment DOM extracts, a third peak (III) was observed near 364 nm. The results show that there is a significant difference in the structure of DOM because of different sources. The humification degree is significantly higher for soil samples than those of sediment samples. The FT-IR spectra of DOM show that structure in sediment DOM is more functional groups than those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 33 publications
0
6
0
4
Order By: Relevance
“…Our previous research has shown that the fulvic-like substances in soil DOM and protein-like material in sediment DOM were quenched by increasing Cu II and Hg II concentrations in Lake Wuliangsuhai. [7,23] A large logarithmic stability constant showed that DOM has a high Cu binding affinity in soils. [23] Because of agricultural drainage, a large number of nonpoint-source pollutants have entered the lake and resulted in changes in the structure of the DOM in the lake sediments.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research has shown that the fulvic-like substances in soil DOM and protein-like material in sediment DOM were quenched by increasing Cu II and Hg II concentrations in Lake Wuliangsuhai. [7,23] A large logarithmic stability constant showed that DOM has a high Cu binding affinity in soils. [23] Because of agricultural drainage, a large number of nonpoint-source pollutants have entered the lake and resulted in changes in the structure of the DOM in the lake sediments.…”
Section: Introductionmentioning
confidence: 99%
“…Todas as bandas selecionadas dos espectros obtidos neste estudo, são bandas comumente encontradas em ácidos húmicos extraídos de solos (STEVENSON, 1994;BENITES et al, 1999;GONZÁLEZ-PÉREZ et al, 2004;MARTINS, 2009;GUO et al, 2012). A banda que se encontra na região de 2.920 a 2.900 cm -1 é atribuída a deformação axial assimétrica de C-H em compostos alifáticos, como metil e metileno.…”
Section: Espectroscopia No Infravermelho Com Transformada De Fourierunclassified
“…A intensidade dessa banda também aumentou, com o aumento da profundidade. A região de 1.280 a 1.200 cm -1 é atribuída a estiramento de C=O de ácidos carboxílicos, segundo alguns autores, essas carbonilas são responsáveis pela complexação de metais presentes no ambiente (PICCOLO; STEVENSON, 1982;HERNÁNDEZ et al, 2006;GUO et al, 2012;. Avaliando a intensidade dessa banda para a área degradada (A4), verificou-se que a intensidade se mantém em todas as profundidades, já para a mata nativa (A5), as intensidades da banda aumentam, conforme aumenta a profundidade.…”
Section: Espectroscopia No Infravermelho Com Transformada De Fourierunclassified
See 2 more Smart Citations